Tuff bands and the stability of coal mine slopes - Koosmen, K (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Tuff bands are a common geological feature in coal deposits throughout Australia and elsewhere throughout the world. They are typically comprised of fine-grained volcanic ash fall sediments, deposited parallel to bedding, in layers from several millimetres to more than several metres in thickness, and most commonly observed in low energy depositional environments which favour their preservation after they are first deposited. Individual tuff layers may be laterally continuous for several hundred kilometres and are almost always continuous across a deposit scale. This makes them particularly useful stratigraphic markers. Whilst tuff bands are generally fine-grained, their geotechnical characteristics may vary widely from durable high strength rock, to clay that can be easily remoulded by hand. Where they exist in a soillike or sheared condition, the presence of tuff bands within the stratigraphic sequence may increase the likelihood for slope instability. Complicating the matter is that shear strength characterisation can be hampered by the inability to collect and preserve samples which are adequate for laboratory shear strength testing. The purpose of this paper is to discuss the geotechnical characteristics, shear strength characterisation and other significant factors for tuff bands in the context of coal mine slope stability. Following this, a number of failure mechanisms are identified for coal mine highwalls, dumped low walls, footwalls and dragline benches, citing several case studies from coal deposits where tuff bands have caused slope instability.
Keywords: coal mine slope stability